Continuous lateral rotational therapy in thoracic trauma––A matched pair analysis. Issue 1 (January 2020) - Schieren, Mark; Wappler, Frank; Klodt, Daniel; Sakka, Samir G.; Lefering, Rolf; Jäcker, Vera; Defosse, Jerome
Highlights: After blunt chest trauma, the use of CLRT did not have an impact on respiratory function, gas exchange, duration of mechanical ventilation, ICU or hospital length of stay, or overall patient outcomes. Patient agitation was noticed more frequently in the CLRT group. A high-quality multicentre RCT is required to provide conclusive results. Abstract: Introduction: Given the lack of reliable evidence on the utility of continuous lateral rotational therapy (CLRT) in chest trauma, we performed a single-centre retrospective matched-pair analysis of patients treated either with CLRT or non-continuous manual turning after blunt thoracic trauma. Methods: We included adult patients that were admitted to our level 1 trauma centre from 2010-2014 and presented with severe thoracic injuries (AISThorax ≥3) within 24 h after the injury and required at least 72 h of mechanical ventilation. Patients were either treated with manual turning every 2–4 h or CLRT. To ensure comparable injury severity and a similar risk for posttraumatic respiratory complications, we matched for thoracic injury severity, age, additional injuries (head, abdomen, extremities) and need for massive transfusion. Results: A total of 22 pairs ( n = 44 patients) were successfully matched and analysed. The use of CLRT did not have a statistically significant impact on respiratory function, gas exchange, duration of mechanical ventilation, ICU or hospital length of stay, or overall patient outcomes (e.g. pneumonia, sepsis, ARDS, mortality). During active rotation the level of sedation was lower compared to manual turning (Richmond Agitation Sedation Scale; manual turning: −3.6; CLRT: −4.0; p = 0.01). Patient agitation was noticed more frequently in the CLRT group (manual turning: n = 2 (9%); CLRT: n = 9 (41%); p = 0.02). Discussion: In this well-matched sample, the use of CLRT did not seem to translate into relevant clinical benefits in patients with thoracic trauma in the setting of modern ICU care with the widespread implementation of lung protective ventilation. However, statistical power and generalisability were limited by the small sample size and single centre design. A large RCT is required to provide conclusive results.